2013
DOI: 10.2105/ajph.2012.300941
|View full text |Cite
|
Sign up to set email alerts
|

Community Needs, Concerns, and Perceptions About Health Research: Findings From the Clinical and Translational Science Award Sentinel Network

Abstract: Objectives Women, the elderly, racial/ethnic, and rural populations are underrepresented in research, which leads to findings that are not representative of diverse populations. A “Sentinel Network” of five sites has been implemented to understand health concerns of underrepresented groups, based on the Community Health Worker (CHW) model. Methods Investigators at the five sites (Washington University, U.C. Davis, U. Michigan, U. Rochester, Einstein College of Medicine) and two community-focused national org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 72 publications
(90 citation statements)
references
References 27 publications
5
83
2
Order By: Relevance
“…Consistent with the top health concerns reported by general population African Americans in a national study (Cottler, McCloskey, Aguilar-Gaxiola, Bennett, Strelnick et al, 2013), diabetes and heart disease were identified as top priority health issues to address with African American churchpopulations. This was not surprising, since the top reported health conditions diagnosed were high blood pressure (44%), high cholesterol (26%), and diabetes (19%), which were similar to findings in the Whitt-Glover, Porter, Yore, Demons, Goldmon et al study with church members (2014).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Consistent with the top health concerns reported by general population African Americans in a national study (Cottler, McCloskey, Aguilar-Gaxiola, Bennett, Strelnick et al, 2013), diabetes and heart disease were identified as top priority health issues to address with African American churchpopulations. This was not surprising, since the top reported health conditions diagnosed were high blood pressure (44%), high cholesterol (26%), and diabetes (19%), which were similar to findings in the Whitt-Glover, Porter, Yore, Demons, Goldmon et al study with church members (2014).…”
Section: Discussionmentioning
confidence: 52%
“…Additionally, HNAs can help identify barriers, facilitators, and community input on the importance and feasibility of potential multisectoral (e.g., churches, schools, businesses) and multilevel intervention strategies (e.g., individual, group, organization, community) to address health issues. HNA benefits can include early community buy-in and commitment to address health issues, better resource allocation through community partnerships, improved validity of procedures, and improved development of culturally-appropriate health promotion intervention strategies that can positively impact health outcomes (Cottler, McCloskey, Aguilar-Gaxiola, Bennett, Strelnick et al, 2013; Fawcett, Suarez de Balcazar, Whang-Ramos, Seekins, Bradford et al, 1988; Lillie-Blanton & Hoffman, 1995; Sharma, Lanum, & Suarez-Balcazaar, 2000; Wright, Williams, & Wilkinson, 1998). …”
Section: Introductionmentioning
confidence: 99%
“…Participants were recruited from health fairs, grocery stores, bus stops, community events and other locations in North Central Florida (Cottler et al, 2013). CHWs, lay community members from the target communities, interviewed participants using the Health Intake questionnaire, developed and extensively piloted to ensure cultural relevance, clarity, and practicality (Cottler et al, 2013). Information in this analysis includes: self-reported history of current or previous STIs, illicit drug use, prescription opioid use, and general socio-ecological variables.…”
Section: Methodsmentioning
confidence: 99%
“…Traditional CPER approaches have involved intensive face-to-face communication formats to promote similar bi-directional dialogue between researchers, community members, and other stakeholders [6][7][8]; yet these approaches limit audience reach and can restrict participation due to constraints of time, geography, and weather. As a result, the Podcast presentations can stimulate bi-directional dialog about important community health topics between community and healthcare stakeholders.…”
Section: This Strategy Fits Well Into the Principles Of Community Andmentioning
confidence: 99%